Diagnostic and Prognostic Values of Serum EpCAM, TGM2, and HE4 Levels in Endometrial Cancer - Lan, Ting; Mu, Chunyan; Wang, Zhongcheng; Wang, Yue; Li, Ying; Mai, Yueqin; Li, Shibao; Xu, Hao; Gu, Bing; Luo, Lan; Ma, Ping (Frontiers in Oncology, 2020)
Objectives: This study aims to investigate the diagnostic and prognostic values of EpCAM, TGM2, and HE4 in endometrial cancer (EC). Methods: In this study, 42 patients diagnosed with EC (EC group), 41 patients diagnosed with myoma (benign group), and 43 healthy women (healthy group), who applied to Affiliated Hospital of Xuzhou Medical University between March 2018 - September 2019 were recruited. Serum EpCAM, TGM2, and IL-33 levels were measured by ELISA, while serum HE4 and CA-125 levels were measured by ECLIA. The serum markers listed above were also measured in 12 paired pre- and post-operative EC patients. The diagnostic and prognostic values of serum markers were analyzed. Results: The serum EpCAM, TGM2, HE4, CA-125, and IL-33 levels were signiﬁcantly higher in the EC group. The sensitivity and specificity of combined detection of EpCAM and HE4 was 92.86% and 69.05%, which were significantly higher than using a single marker or other combinations. Among these markers, serum HE4 levels were significantly higher in patients with myometrial invasion, metastasis, and lymphovascular invasion (p=0.006, p=0.0004, p=0.0004, respectively). And serum TGM2 levels were significantly decreased in post-operative than that of pre-operative EC patients (p<0.001). Conclusions: The combination of EpCAM and HE4 showed the highest specificity and sensitivity in the diagnosis of EC. HE4 was successful in the detection of high-risk individuals preoperatively. Additionally, TGM2 might be a prognostic factor for EC.